Transcriptome Analysis Reveals Catabolite Control Protein A Regulatory Mechanisms Underlying Glucose-Excess or -Limited Conditions in a Ruminal Bacterium, Streptococcus bovis - Jin, Yaqian; Fan, Yaotian; Sun, Hua; Zhang, Ying; Wang, Hongrong (Frontiers in Microbiology, 2021)
Ruminants may suffer from rumen acidosis when fed with high concentration diets due to the higher proliferation and overproduction of lactate by Streptococcus bovis. The catabolite control protein A (CcpA) regulates the transcription of lactate dehydrogenase (ldh) and pyruvate formate-lyase (pfl) in S. bovis, but its role in response to different carbon concentrations remain unclear. To characterize the regulatory mechanisms of CcpA in S. bovis S1 at different levels of carbon, herein, we analyzed the transcriptomic and physiological characteristics of S. bovis S1 and its ccpA mutant strain grown in glucose-excess and glucose-limited conditions. A reduced growth rate and a shift in fermentation pattern from homofermentation to heterofermentation were observed under the glucose-limited condition as compared to glucose-excess condition, in S. bovis S1. Additionally, the inactivation of ccpA significantly affected the growth and end metabolites in both conditions. For the glycolytic intermediate, fructose 1,6-bisphosphate (FBP), the concentration significantly reduced at lower glucose conditions; its concentration decreased significantly in the mutant. Transcriptomic results showed that about 46% of the total genes were differentially transcribed between the wild-type strain and ccpA mutant strain grown in glucose-excess conditions; while only 12% genes were differentially transcribed in glucose-limited conditions. Different glucose concentrations led to the differential expression of 38% genes in the wild-type strain, while only half of these were differentially expressed in the ccpA-knockout strain. KEGG enrichment analyses showed that the substrate glucose concentration significantly affected the gene expression in histidine metabolism, nitrogen metabolism, and some carbohydrate metabolism pathways. The deletion of ccpA affected several genes involved in carbohydrate metabolism, such as in glycolysis, pyruvate metabolism, fructose, and mannose metabolism, as well as in fatty acid biosynthesis pathways in bacteria grown in glucose-excess conditions; this effect was attenuated under glucose-limited conditions. Overall, these findings provide new information on gene transcription and the metabolic mechanisms associated with substrate glucose concentration and validate the important role of CcpA in the regulation of carbon metabolism in S. bovis S1 at differential glucose availability.